A Review of Parent-Implemented Early Start Denver Model for Children with Autism Spectrum Disorder - Rong-An Jhuo; Szu-Yin Chu (MDPI AG, 2022)
The purpose of this review is to provide an overview of findings from selected research published between 2012 and 2022 in English-language peer-reviewed journals to evaluate the effectiveness of the parent-implemented Early Start Denver Model (P-ESDM). Thirteen studies used quantitative methods to examine the relationship between variables. We considered four categories of variables in the analysis: child characteristics, intervention intensity and duration, child outcome measures, and parent-related outcome measures and parental fidelity. The findings revealed positive child-parent-related outcomes. In addition, the quality of implementation, relating to parent fidelity, should be considered when evaluating the efficacy of the intervention. However, only half the studies revealed that the standard benchmark for acceptable fidelity was being achieved. Implications for future research and practice are discussed.